Analysis of The Influence of Perceptions of Price and Service Quality on Consumer Satisfaction in Modern Retail - Anwar, Moh. Nuril; Imeliyanti, Eka; Indrawati, Dwi Risqiani; winanti, winanti; Goestjahjanti, Francisca Sestri; Singgih, Eman; Farhan, Akhmad; Sopyan, Dedi; Mendrofa, Yeremia; Hasna, Shofwatun (Journal of E-business and Management Science, 2024)
This research aims to determine the impact of price perceptions and service quality on consumer satisfaction in the context of modern retail business. The method used is a quantitative method, with a population of modern retail customers with a sample of 60 people in some modern retail customers and a sampling technique using the Slovin formula through questionnaire data with a Likert scale. Research refers to the perception that price has an influence of 70.4%, which has the strongest effect on consumer satisfaction and the remaining 29.6% comes from other factors. Then service quality also has an influence of 67.9% on consumer satisfaction and the remaining 32.1% comes from other factors. Then the 2 influences between price perception and service quality have an influence of 74.0% on consumer satisfaction and the remaining 26.0% comes from other factors. Based on the results of the analysis of the data that has been studied, it can be concluded that (1) price perception has a significant effect on consumer satisfaction which can be seen from t count > t table (13.074 > 2.00247). (2) service quality has a significant effect on consumer satisfaction which can be seen from t count > t table (11.077 > 2.00247). And (3) there is a significant influence between service quality and price perception on consumer satisfaction. It can be seen from the results that f count > f table, namely 100.298 > 3.16. Service quality and price perception have a significant positive influence on increasing consumer satisfaction at Modern Retails. The aim of this research study is to reveal the relationship between price perceptions, service quality and consumer satisfaction in modern retail, with achievemen